The Relationship Between Bicycle Saddles and The Incidence of Erectile Dysfunction In Men : A Systematic Review - Bimo Dono (Brawijaya Journal of Urology, 2024)
Objectives. There is conflicting evidence about the relationship between bicycle saddle type and erectile dysfunction (ED). The main limitation of some previous studies is the lack of a validated measure of ED.Methods. We searched several databases from an English-language medical literature review that was made of publications in peer review journals, including published abstract presentations at major medical meetings, using a variety of search terms relating to “bicycle saddle” and “erectile dysfunction”.Results. After systematic evaluation of 359 studies, 7 studies met our inclusion criteria. In general, cycling significantly reduced perineal oxygen pressure levels (p<0.05). When comparing between studies, cycling more than 3 hours per week was an independent relative risk (RR=1.72) of moderate to severe ED. In a narrower saddle, when examining perineal oxygen pressure, there was a decrease, where it was found that p<0.001, where significantly a narrower saddle increased compression at the perineal saddle interface which disrupted penile hemodynamics.Conclusions. Limited evidence supports a positive correlation between narrower bicycle saddles and compression of the perineal arteries which causes occlusion of penile perfusion, penile blood flow and can lead to endothelial damage and causes erectile dysfunction. Long bike rides with seated positions might cause temporary penile blood flow reduction due to perineal artery pressure, resulting in decreased erectile function. However, this issue usually resolves quickly when pressure is relieved. Heterogeneity between studies suggests the need for further investigation of specific saddle types for cyclists and the measurement.